Cover crops competition for water in vineyards: case studies in Mediterranean terroirs - Lopes, C.M. (2016)
Vineyard cover cropping is a cultural practice widely used in many of the world’s winegrowing regions being one of the most recommended practices to face climate changes and to promote vineyard environmental sustainability. The benefits of using cover crops are many ranging from environmental protection (e.g. control of soil erosion, enhancement of soil structure and biodiversity, sequestering carbon) to vineyard management, including control of vigor and improvement of berry composition. Despite those potential benefits, the adoption of cover crops in Mediterranean non-irrigated vineyards has been limited by the concern of excessive water competition between cover crops and vines. However the level of this competition should be better understood as in warm and dry terroirs, like the case of Mediterranean winegrowing regions, water competition by the cover crops is effective mainly during spring. During summer, the almost absence or rainfall induces the dry out of the sward vegetation which residues became dead mulch that can even reduce soil evaporation. Furthermore, some research has also demonstrated that, after some years of competition with swards, the vines were able to develop deeper roots, therefore increasing the capacity for water extraction from deeper soil layers. In order to further elucidate the above mentioned topics, in this paper data on water use and grapevine performance obtained in three floor management experiments (soil tillage vs. inter-row swards), carried out in three different winegrowing regions of the Mediterranean Portugal (covering rainfed and irrigated vineyards), will be presented. Discussion will be focus on water competition by the swards and corresponding effects on grapevine vigor, yield and berry composition. The effect of terroir on grapevine responses will be also underlined. From the data presented it can be concluded that cover crops is a vineyard management practice that can have a positive influence on water use efficiency, either by preventing vine excessive vigor when water is fully available during spring or by maximizing the volume of soil explored by vine roots through the enhancement of the exploitation of soil water reserves into deeper layers. However, in the case of low vigor vineyards located in dry terroirs, the degree of water competition between cover crops and vine must be carefully monitored and managed (e.g. by increasing mowing frequency, reducing the sward strip and/or choosing less competitive species) and adjustments in conventional irrigation management are necessary in order to avoid detrimental effects on grapevine yield and longevity.